Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Vespoidea, Pompilidae - Gadallah, Neveen S.; Schmid-Egger, Christian; Brothers, Denis J. (Zootaxa, 2020)
An updated checklist of the Arabian species of Pompilidae is provided here. The list includes 119 identified valid species in 35 genera and three subfamilies: Ceropalinae (1 genus, 6 species), Pepsinae (6 genera, 26 species) and Pompilinae (28 genera, 87 species). Distributions, both on the Peninsula and extra-limital, are provided for each species and subspecies; 22 species (18%) are confined to the Arabian Peninsula.